Sustainability Accounting and Tax Compliance Education: PT Enha Bena Nusantara - Nugrahani, Novi; Putra, Indra Lukmana; Utami, Kuni; Winarto, Edi; Syuliswati, Atika; Widati, Suryan; Afiatin, Yunia (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This program aims to enhance understanding and implementation of sustainability accounting and tax compliance at PT Enha Bena Nusantara, addressing literacy gaps and integration challenges faced by SMEs. Method: A participatory approach was applied through a two-day training, interactive discussions, and case studies. Data were collected using pre- and post-training questionnaires, observations, and interviews, analyzed through descriptive statistics and thematic analysis. Practical Applications: The five-stage educational model includes assessment, module development, workshop implementation, evaluation, and replication. Materials cover sustainability accounting, bookkeeping, tax regulations, and exercises linking reporting to compliance. Conclusion: The intervention significantly improved participants’ knowledge and awareness of sustainability accounting and tax obligations. The program offers practical solutions to strengthen transparency, fiscal compliance, and long-term competitiveness for SMEs.